2006
DOI: 10.1097/01.psy.0000221378.09239.6a
|View full text |Cite
|
Sign up to set email alerts
|

Age and Ethnicity Differences in Short-Term Heart-Rate Variability

Abstract: Young African Americans manifested a pattern of HRV response similarly to older Caucasian Americans. These results suggest that young African American individuals might show signs of premature aging in their autonomic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 43 publications
3
69
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19] Different time domain components of HRV has been used as marker of overall cardiac autonomic activity. The task force guideline for HRV analysis have demonstrated the interpretation of these parameters to understand the status, behavior and the balance between sympathetic and parasympathetic function due to their continuous interaction.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Different time domain components of HRV has been used as marker of overall cardiac autonomic activity. The task force guideline for HRV analysis have demonstrated the interpretation of these parameters to understand the status, behavior and the balance between sympathetic and parasympathetic function due to their continuous interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some research has reported findings of lower HRV in African Americans relative to Whites (e.g., Choi et al, 2006; Lampert et al, 2005), whereas other research has shown higher HRV in African Americans (Liao et al, 1995; Wang et al, 2005). More recently, Hill and colleagues (2015) conducted a meta-analysis of 17 studies comprising more than 11,000 total participants, reporting ethnic differences in basal HRV between African Americans and Whites.…”
mentioning
confidence: 99%
“…Factors including age, body mass index, alcohol consumption, cigarette smoking, and even ethnicity can affect autonomic function. Mentioned factors lead to different HRV in both groups (Choi et al, 2006;Elsenbruch, Harnish, & Orr, 1999;Hogarth, Graham, Mary David, & Greenwood, 2009;Kuo et al, 1999;Moodithaya & Avadhany, 2012;Palisso et al, 1999;Regitz-Zagrosek, Lehmkuhl, & Weickert, 2006;Tanaka, Kimura, Goyagi, & Nishikawa, 2004;Uusitalo et al, 2007). In the current research, the focus was on possible effects of gender on HRV and autonomic dysfunction in epileptic patients.…”
Section: Discussionmentioning
confidence: 98%